2018
DOI: 10.3126/mjpahs.v1i2.23396
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Subclinical and Overt Hypothyroidism

Abstract: Background: Sub-clinical hypothyroidism (SCH), overt hypothyroidism and metabolic syndrome (MetS) are recognized risk factors for atherosclerotic cardiovascular disease and Type 2 diabetes mellitus (DM- II).Thyroid function affects MetS parameters including blood pressure (BP), fasting blood sugar (FBS), serum triglycerides (TG) and high density lipoprotein cholesterol (HDL-C). But the relationship between MetS and thyroid functions is yet to be identified clearly. The present study is to investigate the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A 3-year population-based cohort study showed that both overt and subclinical hypothyroidism, especially in older people, are associated with metabolic syndrome. 54 This finding was mirrored by that of a hospital-based cross-sectional study conducted in Nepal, 55 and another cross-sectional study conducted in India showed that overt hypothyroidism is associated with a higher risk of metabolic syndrome. 56 Finally, a population-based survey conducted in Italy showed a positive correlation between circulating TSH and triglyceride concentrations, and positive relationships between free thyroxine (FT4) and the components of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 83%
“…A 3-year population-based cohort study showed that both overt and subclinical hypothyroidism, especially in older people, are associated with metabolic syndrome. 54 This finding was mirrored by that of a hospital-based cross-sectional study conducted in Nepal, 55 and another cross-sectional study conducted in India showed that overt hypothyroidism is associated with a higher risk of metabolic syndrome. 56 Finally, a population-based survey conducted in Italy showed a positive correlation between circulating TSH and triglyceride concentrations, and positive relationships between free thyroxine (FT4) and the components of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 83%